Analisa aktivitas antioksidan serta eksplorasi flavonoid dari daun Synsepalum dulcificum sebagai inhibitor aldosa reduktase: Analysis of antioxidant activity and exploration of flavonoid from Synsepalum dulcificum leaves as aldose reductase inhibitors - Anggono, Wike Adhi; Susilowati, Retno; Jannah, Akyunul (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2024)
Synsepalum dulcificum leaves are known to contain bioactive compounds, especially flavonoids, which have important biological activities, including inhibition of aldose reductase, an enzyme involved in diabetes complications. This study aims to explore the potential of flavonoids from Synsepalum dulcificum leaves as antioxidants and inhibitors of the aldose reductase enzyme. The methods used in this study include in-vitro tests with the DPPH method to evaluate antioxidant activity and molecular docking to predict the interaction between flavonoids and the aldose reductase enzyme. Leaf extracts were isolated using the maceration method with 70% ethanol, and active compounds were identified through LC-MS analysis. Molecular docking tests were performed using PyRx, PyMol, and BIOVIA: Discovery Studio Visualizer software. The results showed that Synsepalum dulcificum leaf extract had very strong antioxidant activity with an IC50 value of 11.4108 Î¼g/mL. Molecular docking results revealed that the compounds morin and pinostrobin had a stronger binding affinity to aldose reductase than the standard ligand sorbinyl. In conclusion, flavonoids from Synsepalum dulcificum leaves have great potential as antioxidant agents and aldose reductase inhibitors, which can be further developed as natural therapeutic candidates to prevent diabetic complications.